Rheological Analysis of The Aging Behavior of Short-Term Aged Pure And SBS-Modified Asphalt Binders - Özdemir, Ahmet Münir (Fırat Üniversitesi, 2025)
Flexible pavements consist of a bituminous binder and certain graded aggregate. The performance of the bitumen determines the overall pavement performance. Bitumen undergoes short-term aging from production to application, accounting for most of its total aging during service life. This study rheologically investigates the short-term aging behavior of 70/100 pure bitumen and SBS-modified bitumen. Frequency Sweep test was performed on bitumen samples with Dynamic Shear Rheometer (DSR) device at different frequency (0.01-10 Hz) and temperature (40, 50, 60, 70°C) ranges. The complex modulus and complex viscosity master curves of the binders were obtained by processing the experimental data and the curves were subjected to rheological model analysis. The study showed that SBS modification enhanced aging resistance by preserving elastic properties. Moreover, the master curves were applied to rheological models with high accuracy.

Esnek üstyapılar bitümlü bağlayıcı ve uygun gradasyonda agreganın karışımından elde edilmekte ve bitümün performansı kaplamanın nihai performansı üzerinde belirleyici faktör olmaktadır. Bitüm, üretilmesinden uygulanmasına kadar geçen sürede kısa dönemli yaşlanmaya maruz kalır ve bu yaşlanma servis ömrü boyunca meydana gelecek yaşlanmanın büyük kısmını oluşturur. Bu sebeple kısa dönemli yaşlanma davranışı oldukça önemlidir. Bu çalışmada çeşitli analitik yaklaşımlar ile 70/100 saf bitüm ve Stiren-Butadien-Stiren (SBS) modifiyeli bitümün yaşlanma dayanımları reolojik olarak incelenmiştir. Bitüm numuneleri üzerinde Dinamik Kayma Reometresi (DSR) cihazı ile farklı frekans (0.01-10 Hz) ve sıcaklık (40, 50, 60, 70°C) aralıklarında Frekans Tarama testi uygulanmıştır. Deneysel veriler işlenerek bağlayıcıların kompleks modül ve kompleks viskozite ana eğrileri elde edilmiş, eğriler reolojik analizlere tabi tutulmuştur. Sonuçlar, SBS modifikasyonu ile yaşlanma esnasında elastik özelliklerin korunma kabiliyetinin artırılarak yaşlanma direncinin iyileştirildiğini göstermiştir. Ayrıca, ana eğriler reolojik modellere yüksek doğrulukta uygulanmıştır.
Kısa Dönem Yaşlandırılmış Saf ve SBS Modifiyeli Asfalt Bağlayıcıların Yaşlanma Davranışlarının Reolojik Araştırması
Keywords: Transportation Engineering; Ulaştırma Mühendisliği